EFEKTIVITAS METODE GERAK DAN LAGU TERHADAP MINAT BELAJAR ANAK USIA 5-6 TAHUN DI PAUD QU AL-AMALIYAH KARAWANG - Neng Via Selpiani; Syafrida, Rina; Riana, Nancy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning interest of children aged 5–6 years at PAUD Qu Al-Amaliyah Karawang, as indicated by their limited attention, interest, enjoyment, and active participation during learning activities. The study aimed to determine children's learning interest before and after the implementation of the movement and song method and to identify the differences in learning interest following the intervention. This study employed a quantitative approach using a One Group Pretest–Posttest Design. The participants consisted of 22 children aged 5–6 years from Group B at PAUD Qu Al-Amaliyah Karawang. Data were collected through an observation checklist of learning interest and analyzed using descriptive statistics and the Paired Sample t-test. The results showed that the mean pretest score of children's learning interest was 40.23, which increased to 66.45 after the implementation of the movement and song method (posttest). The hypothesis test yielded a t-value of -65.713 with a significance value (Sig. 2-tailed) < 0.001, indicating a statistically significant difference between the pretest and posttest results. The findings indicate an improvement in children's learning interest following the implementation of the movement and song method, as reflected in increased attention, interest, enjoyment, and active participation during learning activities. However, because this study employed a One Group Pretest–Posttest Design without a control group, the findings indicate an improvement after the intervention but cannot entirely rule out the influence of other factors, such as maturation, testing effects, or classroom conditions. Therefore, the movement and song method has the potential to support the improvement of learning interest among children aged 5–6 years at PAUD Qu Al-Amaliyah Karawang.